2012
DOI: 10.4102/sajim.v14i1.503
|View full text |Cite
|
Sign up to set email alerts
|

Using communities of practice towards the next level of knowledge-management maturity

Abstract: Background: Effective communities of practice undoubtedly impact organisations’ knowledge management and contribute towards building a learning-organisation culture. Communities of practice represent an environment conducive to learning and for exchanging ideas, and they are a formal learning forum. However, the level of organisational learning to which communities of practice contribute is difficult to measure.

Objectives: The research was conducted to analyse the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In contrast, tacit knowledge acquisition, in the opinion of Wenger (2006), is linked to Communities of Practice. Chetty and Mearns (2012) conducted a study to analyse the impact of communities of practice (CoPs) on building a learning organization. Using Multichoice South Africa as a case study, the results revealed that CoPs can contribute towards creating a learning organization culture.…”
Section: Organizational Learning Activities In Public Sector Organizationsmentioning
confidence: 99%
“…In contrast, tacit knowledge acquisition, in the opinion of Wenger (2006), is linked to Communities of Practice. Chetty and Mearns (2012) conducted a study to analyse the impact of communities of practice (CoPs) on building a learning organization. Using Multichoice South Africa as a case study, the results revealed that CoPs can contribute towards creating a learning organization culture.…”
Section: Organizational Learning Activities In Public Sector Organizationsmentioning
confidence: 99%
“…But the essential element remains the participant. CoP requires different types of resources (human, financial, logistics, informational), so it's important for any given organizations to answer the crucial question of return on investment, namely benefits and impacts generated [13], [14]. To answer to the concern of those who carry out this type of initiative in different organizational contexts (large or medium-sized enterprises, manufacturing companies, research centers, professional groups, etc.…”
Section: Km Levelmentioning
confidence: 99%
“…However, knowledge management, and particularly CoPs require the development of a dedicated assessment framework that favors the perspective of users or participants. In addition, since it is recognized that assessment is a process, impacts are assumed to evolve over time [14]. It is therefore important to integrate the temporal dimension, the diversity of the forms of assessment induces to identify the appropriate methodology.…”
Section: What Dimensions Are At Stake To Assess Cop$? a Problematic Reviewmentioning
confidence: 99%
“…According to Chetty and Mearns (2012), virtual environments present effective knowledge-management platforms through communities of practice. These virtual environments assist when the participants are in geographically dispersed areas.…”
Section: Environmental and Virtualmentioning
confidence: 99%